2021
DOI: 10.5296/jei.v7i1.18508
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Distance Education in COVID-19 Period: Turkish Pre-Service Teachers’ E-Learning Attitudes and Readiness Levels

Abstract: In this study, pre-service teachers’ attitudes and readiness towards e-learning during the COVID-19 pandemic were examined. This research was carried out in the Fall Semester of the 2020-2021 Academic Year, with the participation of 519 pre-service teachers from Balıkesir University Necatibey Faculty of Education and Faculty of Sport Sciences, Department of Physical Education and Sports Education. In the collection of data, the General Attitude Scale towards e-learning developed by Haznedar and Baran (2012) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
2
0
2
Order By: Relevance
“…Also, these materials made PSTs more prepared before engaging in Zoom synchronous class. These findings were closely matched with previous studies' results (Balci et al, 2021;Ceylaner & Karakus, 2018;Kim & Choi, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, these materials made PSTs more prepared before engaging in Zoom synchronous class. These findings were closely matched with previous studies' results (Balci et al, 2021;Ceylaner & Karakus, 2018;Kim & Choi, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…They liked the combined use of the LMS and Google Drive with online FL because they believed that it was a helpful educational tool. Previous studies have also confirmed that FL can encourage students to explore materials in advance so that they can be more self-directed learners by using the LMS (Balci et al, 2021;Ceylaner & Karakus, 2018;Kim & Choi, 2018). This study also provided evidence that pre-loaded materials, including pre-recorded online lectures, encourage PSTs to become more independent and self-directed learners through online FL.…”
Section: Discussionmentioning
confidence: 87%
“…Namun, kajian oleh Rustam et al, (2020) mendapati guru pelatih mempunyai sikap yang berbeza antara kognitif dan efektif iaitu sikap positif dalam aspek kognitif tetapi sikap negatif dalam aspek afektif dan tingkah laku semasa pembelajaran dalam talian. Kenyataan yang sama oleh Balci et al, (2021) mendapati guru pelatih mempunyai sikap negatif terhadap pembelajaran dalam talian. Hal ini menunjukkan bahawa sikap guru pelatih terhadap PdPR adalah tidak sama dan dipengaruhi oleh faktor jantina.…”
Section: Profil Respondenunclassified
“…Begitu juga hubungan antara pemboleh ubah sikap guru pelatih dan perlaksanaan PdPR dalam kalangan guru pelatih Geografi semasa latihan mengajar, didapati hubungan yang sederhana antara kedua-duanya dengan nilai r = 0.494 dan p = 0.000 (p<0.01). Hasil kajian ini selari dengan kajian oleh Balci et al, (2021) mendapati hubungan yang signifikan antara sikap guru pelatih terhadap pembelajaran dalam talian dengan kesediaan guru pelatih dalam PdPR. Penemuan Sepulveda-Escobar & Morrison (2020) mendapati guru pelatih menyatakan bahawa pengalaman pengajaran secara dalam talian ini akan menyumbang secara positif kepada pendidikan guru dan kerjaya masa depan mereka.…”
Section: Analisis Korelasi Pengetahuan Sikap Kemahiran Motivasi Denga...unclassified
“…Although it has some drawbacks, it seems that e-Teaching is a promising mode of delivery. From their study, Balci et al (2021) concluded that e-learning readiness was an effective factor in the adoption of the e-Learning process. For example, Al-Anezi and Alajmi (2021) reported a high acceptance level to implement distance learning tools among English language instructors in tertiary education in Kuwait.…”
Section: Teachers' Attitudes Towards Online Educationmentioning
confidence: 99%